2016
DOI: 10.1586/17474086.2016.1146584
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Large B-cell lymphoma: Prognostic markers and their impact on therapy

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common type of Non-Hodgkin lymphoma (NHL). DLBCL is clinically, pathologically and molecularly heterogeneous disease. Various clinical, pathological and molecular markers have been developed to characterize the disease. Based on these characterizations, new targeted agents are being investigated to optimize the treatment and improve the outcomes of DLBCL. Enhanced molecular understanding, invention of targeted agents and immunotherapy has opened the doors for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…Among 13 elder (≥70 years) patients with partial or complete response to MTX/rituximab-based induction, the median PFS has not been reached after 31.6 months of follow-up and no treatment-related death has been reported. [ 54 ] A similar result was found in relapsed patients administered maintenance lenalidomide. [ 55 ] Finally, a case report reported that nivolumab maintenance resulted in long-term remission of 18 months in a patient with multiple PCNSL relapses.…”
Section: Consolidation Treatmentsupporting
confidence: 64%
“…Among 13 elder (≥70 years) patients with partial or complete response to MTX/rituximab-based induction, the median PFS has not been reached after 31.6 months of follow-up and no treatment-related death has been reported. [ 54 ] A similar result was found in relapsed patients administered maintenance lenalidomide. [ 55 ] Finally, a case report reported that nivolumab maintenance resulted in long-term remission of 18 months in a patient with multiple PCNSL relapses.…”
Section: Consolidation Treatmentsupporting
confidence: 64%
“…These efforts have resulted in only slight improvements in characterization of low‐risk and high‐risk patients. In addition, various biomarkers, gene signatures, and molecular techniques could not replace the prognostic value of the clinically based IPI …”
Section: Introductionmentioning
confidence: 99%
“…Non-Hodgkin's lymphoma (NHL) is a clonal proliferative disease of Β, T or natural killer cells which originate from lymph nodes or extranodal lymphatic tissue [1]. NHL comprises 4% of newly diagnosed cancer, and 90 % of lymphomas.…”
Section: Introductionmentioning
confidence: 99%